Gender as a category entangled in the matrix of power and gender resistance potential - Bielska, Ewa (Wydawnictwo Naukowe UAM, 2015)
The subject of presented analysis is gender treated as a social category entangled in power relations. There are presented main social matrices of the gender-based power practices and it’s institutional and extrainstitutional, structural and individual expressions and consequences. The attention is focused at the classical conceptions of power and the perspectives of using it’s elements in the analysis of gender-based discipline practices in modern and postmodern society. There are also indicated―connected with queer culture―resistance strategies realized by using gender symbols and stereotypically perceived roles.
Keywords: gender; power; discipline; resistance; sexism; heterosexism; homophobia